Historia, identidad y mesianismo en la mitología andina - Gutierrez Estevez, Manuel (1984)
The author conducts a paradigmatic analysis of six versions of the competitions between Inkarrí and Collarrí. He shows that the meaning of the competition is not in, the victory but in the basis of the exchange between the peoples headed by Inkarrí and Collarí. The asymmetric exchange, contradictory in itself, expressed and transmitted through a series of ritual competitions, constitutes the object of the myth. He then argues, briefly and hypothetically, that the essence of the myth of the defeat of Inkarrí at the hands of Españarrí would not be the expression of a messianic expectation, but that of a search for reciprocity necessarily asymmetric, between traditional Andean culture and Spanish culture. The author finally alludes to a ritual, The race of the Three Wise Men, in, San Pablo, Canchis Province, which brings together what the myths had separated: Inkarrí and Collarrí competitions on the one hand, combat between Inkarrí and Españarrí on the other. The three kings - Inkarrí, Collarrí and Mistirey - compete and in the expected effects depending on which of them has been the winner - good or bad agricultural year - their complementarity and reciprocity are expressed.